2012
DOI: 10.2188/jea.je20110095
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atherosclerosis-Related Risk Factors and Diseases in the Philippines

Abstract: BackgroundWe conducted a survey in 2008 to measure the prevalence of lifestyle-related diseases and risk factors in Philippine adults.MethodsStratified multistage sampling was used to cover the entire Philippine population of adults aged 20 years or older. Using health questionnaires, anthropometric measurements, and blood examinations, the prevalences of atherosclerosis-related risk factors and diseases were determined. Survey results were compared with those obtained in 2003.ResultsOut of 7700 eligible subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 17 publications
5
41
0
1
Order By: Relevance
“…A high proportion of the respondents had correctly identified some of the known risk factors, preventive measures, and signs and symptoms of CVD. Most had mentioned eating fatty or oily food, cigarette smoking, and lack of exercise as CVD risk factors, which were consistent with the findings in related studies and surveys [18][19][20][21]. Yet, the proportions of those who did not identify stress, salty diet, and genes as CVD risk factors, along with those who identified mosquito bites and sharing utensils as risk factors, are indicative of some knowledge gaps.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A high proportion of the respondents had correctly identified some of the known risk factors, preventive measures, and signs and symptoms of CVD. Most had mentioned eating fatty or oily food, cigarette smoking, and lack of exercise as CVD risk factors, which were consistent with the findings in related studies and surveys [18][19][20][21]. Yet, the proportions of those who did not identify stress, salty diet, and genes as CVD risk factors, along with those who identified mosquito bites and sharing utensils as risk factors, are indicative of some knowledge gaps.…”
Section: Discussionsupporting
confidence: 80%
“…Among the respondents, the proportion of current smoking behaviour at 36.0% was lower than that of the proportion among males in the general population in the Philippines ranging from 44.7% to 73.1% [19][20][21]. However, previous studies had shown that smoking behaviour was higher in the seafaring population than in the general population [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Most surveys over the last decade put the prevalence of hypertension at between 19-30% in the West [8] and 25-48% in the East [9][10][11][12][13][14][15][16][17][18][19]. Most published national surveys over the last decade has been from outside the West.…”
Section: Prevalence and Awareness Of Hypertensionmentioning
confidence: 99%
“…2 According to two Philippine surveys, National Nutrition and Health Survey I (NNHeS I) and NNHeS II, conducted in 2003 and 2008, respectively, the overall prevalence of diabetes based on FBG increased from 3.3% (2003) to 3.9% (2008), while the true prevalence of diabetes based on FBG and questionnaire responses, increased from 4.4% (2003) to 5.2% (2008). 3 The International Diabetes Federation (IDF) reported that the prevalence of diabetes in adults in the 20-79 year age group in the Philippines was 6.5% and estimated it to be 7.9% by 2025. 4 However, a recent study by Soria et al, carried out in a cohort of 1749 individuals has reported much higher 9-year (1999-2007) incidence and prevalence rates of type 2 DM at 16.3% and 28.0% respectively.…”
Section: Introductionmentioning
confidence: 99%